Postmodern evolutionary framework for chronic diseases – cultural evolution allows multicausal explanations - Lange, Axel; Kaiser, Ulrike; Pradier, Bruno; Pogatzki-Zahn, Esther M.; Segelcke, Daniel (Frontiers in Ecology and Evolution, 2025)
Non-communicable diseases—such as cardiovascular diseases, cancer, respiratory diseases, diabetes, and chronic pain—pose significant global health challenges, causing millions of deaths annually. Traditionally, holistic frameworks have been developed to analyse these conditions. Although integrating biological, psychological, and social factors, the biopsychosocial model suffers from a lack of detail and practical application. By incorporating cultural evolutionary perspectives, we can better understand how evolutionary influences affect disease susceptibility and persistence. We propose a postmodern, evolutionary-informed biopsychosocial framework that draws on insights from cultural evolution and niche construction theory. This approach spans multiple evolutionary time scales—from immediate behavioural adaptations to long-term genetic and cultural changes—and provides a nuanced view of health condition dynamics. Ultimately, this interdisciplinary framework advances strategies for prevention and treatment by offering a differentiated and effective approach to managing modern health challenges.Lay summaryA new framework combines biological, psychological, and social factors with cultural evolution to better understand long-term conditions like heart disease, cancer, and diabetes. It spans immediate behavioural changes to long-term genetic and cultural influences, offering improved strategies for prevention and treatment.